Efficacy and safety of intradialytic parenteral nutrition using ENEFLUID® in malnourished patients receiving maintenance hemodialysis: An exploratory, multicenter, randomized, open-label study. - Hideyuki Kabasawa; Michihiro Hosojima; Eiichiro Kanda; Miho Nagai; Toshiko Murayama; Miyuki Tani; Satoru Kamoshita; Akiyoshi Kuroda; Yoshihiko Kanno (PLoS ONE)
The objective of this study was to investigate the efficacy and safety of intradialytic parenteral nutrition (IDPN) using ENEFLUID® (310 kcal, 550 mL) in mild-moderate malnutrition patients receiving maintenance hemodialysis. A total of 40 adult patients with a Nutritional Risk Index-Japanese Hemodialysis (NRI-JH) score of 5-10 were enrolled in this multicenter, randomized, open-label study. Patients in the intervention group received IDPN using ENEFLUID® via the dialysis circuit 3 times a week for 12 weeks; those in the control group did not. The primary endpoint was change in serum transthyretin (TTR). The secondary endpoints were changes in nutritional laboratory tests, nutritional parameters, food intake, plasma amino acids, and blood glucose. For both groups, mean age (72.1±11.4 years) and BMI (20.3±3.0), and median NRI-JH score [7.0 (interquartile range, 6-8)], did not differ. One patient withdrew before intervention, leaving 20 intervention and 19 control patients. Mean (95% confidence interval) change in serum TTR (mg/dL) at 12 weeks did not differ between groups: Intervention, 1.0 (-1.1-3.2); Control, -0.3 (-2.4-1.9); Intragroup difference, 1.3 (-1.7-4.3); P = 0.41. The values reflecting protein intake at 12 weeks compared to those on the study initiation day increased in the intervention group [the changes of blood urea nitrogen, 9.4 (2.6-16.2) mg/dL; P = 0.007, and normalized protein catabolic rate, 0.10 (0.02-0.18) g/kg/day; P = 0.02]. Mean food protein intake (g/kg/day) at 12 weeks increased in the intervention group and decreased in the control group, and differed between groups: Intervention, 0.12 (-0.03-0.28); Control, -0.18 (-0.43-0.08); Inter-group difference, 0.30 (0.00-0.60); P = 0.050. No adverse events occurred. In patients with mild to moderate malnutrition receiving ENEFLUID® for 12 weeks as IDPN, serum TTR was not improved, decreases in protein intake was mitigated, no adverse events occurred. Trial registration Name of the registry: Japan Registry of Clinical Trials Registration number: jRCTs031220296.